KEANEKARAGAMAN HOSPES JENIS-JENIS CAPLAK MARGA-MARGA AMBLYOMMA, BOOPHILUS DAN RHIPICEPHALUS (ACARINA: IXODIDAE) YANG TERCATAT MEMARASIT KERBAU DAN SAPI DI INDONESIA - MUNAF, HASAN BASRI (Research Center for Biology-Indonesian Institute of Sciences, 1986)
H.B. MUNAF. 1986.The hosts and species of ticks of the genera Amblyomma, Boophilus and Rhipicephalus recorded parasitizing buffaloes and cattle in Indonesia.Berita Biologi 3 (6) : 287 - 292.About 30 species of mammals,one reptile and Several birds were incriminated as the hosts for seven species of ticks of the genera Amblyomma, Boophilus and Rhipicephalus parasitizing buffa loes artd cattle in Indonesia. Among the ticks, B. microplus and R. pilans: are considered a serious pest to livestocks, whilst A. testudina'rium could become a- potential vector in spreading diseases.A. babirussae was recorded as an endemic species found in Central and South Sulawesi; and R. haemaphysaloides seemed likely to have a limited distribution in the upperpart half of Sumatera only. A key to identify the seven species of ticks listed is given.